An investigation into the achievement of some concepts in social studies among students completing junior secondary education from different types of schools in the western province of Sri Lanka - Rupasinghe, S. (My University, 1978)
The present state system of schools claims to provide equality of opportunity by the provision of an almost uniform education in all schools. All state schools provide a common curriculum without stroaming up to the end of the junior secondary level which till 1977 terminated at garde nine. All sate chools also provide free education. Education in these is through the mother tongue....